Future rainfall and temperature changes in Brazil under global warming levels of 1.5ºC, 2ºC and 4ºC - Santos, Diego Jatobá dos; Pedra, George Ulguim; Silva, Marcelo Guatura Barbosa da; Guimarães Júnior, Carlos Augusto; Alves, Lincoln Muniz; Sampaio, Gilvan; Marengo, José Antônio (Sustainability in Debate, 2020)
The present study analyzes the impacts of global warming of 1.5ºC, 2ºC, and 4ºC above pre-industrial levels in the Brazilian territory. Climate change projected among the different global warming levels has been analyzed for rainfall, temperature and extreme climate indices. The projections are derived from the global climate model HadGEM3-A, from the High-End cLimate Impacts and eXtremes (HELIX) international project, from the United Kingdom, forced by sea surface temperature and sea ice concentration of a subset of six CMIP5 (Coupled Model Intercomparison Project phase 5) global climate models and considering the RCP 8.5 (Representative Concentration Pathways) emissions scenario throughout the 21st century. Projections indicate robust differences in regional climate characteristics. These differences include changes: in the minimum and maximum air temperature close to the surface to all the country’s regions, in extremes of heat, particularly in northern Brazil, in the occurrence of heavy rainfall (Southern and Southeastern regions), and in the probability of droughts and rain deficits in some regions (Northern and Northeastern Brazil).